Canopy leaf area of a mature evergreen Eucalyptus woodland does not respond to elevated atmospheric [CO2] but tracks water availability. (9th February 2016) - Duursma, Remko A.; Gimeno, Teresa E.; Boer, Matthias M.; Crous, Kristine Y.; Tjoelker, Mark G.; Ellsworth, David S.
Abstract: Canopy leaf area, quantified by the leaf area index ( L ), is a crucial driver of forest productivity, water use and energy balance. Because L responds to environmental drivers, it can represent an important feedback to climate change, but its responses to rising atmospheric [CO2 ] and water availability of forests have been poorly quantified. We studied canopy leaf area dynamics for 28 months in a native evergreen Eucalyptus woodland exposed to free‐air CO2 enrichment (the EucFACE experiment), in a subtropical climate where water limitation is common. We hypothesized that, because of expected stimulation of productivity and water‐use efficiency, L should increase with elevated [CO2 ]. We estimated L from diffuse canopy transmittance, and measured monthly leaf litter production. Contrary to expectation, L did not respond to elevated [CO2 ]. We found that L varied between 1.10 and 2.20 across the study period. The dynamics of L showed a quick increase after heavy rainfall and a steady decrease during periods of low rainfall. Leaf litter production was correlated to changes in L, both during periods of decreasing L (when no leaf growth occurred) and during periods of increasing L (active shedding of old foliage when new leaf growth occurred). Leaf lifespan, estimated from mean L and total annual litter production, was up to 2 months longer under elevated [CO2 ] (1.18 vs. 1.01 years; P = 0.05). Our main finding that L was not responsive to elevated CO2 is consistent with other forest FACE studies, but contrasts with the positive response of L commonly predicted by many ecosystem models.